Strategi Council of Palm Oil Producing Countries dalam Melindungi Ekspor Komoditas Kelapa Sawit Negara Anggota Dari Ancaman Kebijakan Proteksionis Uni Eropa - Indriati Safitri; Alfian Hidayat; Sirwan Yazid Bustami (Indonesian Journal of Global Discourse, 2021)
This paper aimsto explain how the strategy of the council of palm oil producing countries (CPOPC) inovercoming problems in the palm oil sector caused by the protectionist policies of the EuropeanUnion. The EU policy is contained in the Renewable Energy Directive II which contains the gradualelimination of the use of palm oil which is categorized as a high risk vegetable oil for deforestation andland conversion. This certainly has a significant impact on the export performance of palm oilproducing countries. Palm oil is a very vital commodity for the sustainability of the global economy.Thus, if faced with threats in the form of protectionist policies, negative campaigns, and discriminationagainst palm oil, it becomes a shared responsibility for oil palm producing countries to fight for theexistence of palm oil in the global market. Through multilateral organizations, in this case, CPOPC isconsidered a strategic step in carrying out economic diplomacy efforts in achieving common goals inovercoming the threat of the EU's RED II policy.